Sensemaking training in preparation for effective mission command in the African battlespace - O'Neil, Sumari; O'Neil, Johnny (Scientia Militaria - South African Journal of Military Studies, 2022)
The South African National Defence Force (SANDF), as a member state of the United Nations, the African Union and the Southern African Development Community, has certain continental and regional responsibilities. It is foreseen that the main areas of influence and operations of the SANDF will be situated in Africa and are referred to as the African battlespace, which holds challenges for deploying military commanders. We argue that the elevated levels of complexity and uncertainty in this context make mission command, as a command approach, especially relevant. The conceptual study on which this article is based, found that mission command is highly suitable to promote a command culture that is flexible yet robust, fosters unity of command at all levels, and simultaneously provides subordinate commanders with the freedom to act decisively when new opportunities are identified. For mission command to be applied in the African battlespace, sensemaking is an important cognitive skill that should form an integral part of the psychological preparation and training of commanders. Recommendations are made for sensemaking development in the current training of commanders in the SANDF.